CFD simulation of wave-in-deck loads on offshore structures - Tunlid, Martin; Olsson, Adam (My University, 2015)
In the offshore industry, physical model tests are common to predict slamming loads and wave impacts, but also to investigate platform motions and structural responses. Unfortunately, creating models and performing experimental tests can be time-consuming and relatively expensive. Problems with scaling effects emerges and reliability of measurement equipment can be questioned. This makes other alternatives interesting and there is a growing need for numerical tools capable of predicting hydrodynamic loads in detail, such as Computational Fluid Dynamics (CFD) programs. A numerical model has the advantage that a simulation can quickly be adapted to changes in geometry or wave conditions, but also it has the possibility to measure physical properties at any location in the computational domain. This motivates the use of CFD solvers to predict wave loads and the objective of this thesis is to use CFD to estimate wave-in-deck loads in simplified situations. A two-dimensional platform deck with a specified air-gap to the free water surface is modelled and in order to verify the feasibility of the CFD software, the deck is subjected to regular incident waves and the vertical lifting force is compared to experimental data. Simulations are performed with four different settings, two wave heights and two wave periods, respectively. A three-dimensional platform is also modelled as an illustrative example to further explore and demonstrate the possibilities of the CFD software. In this case, wave run-up is observed and pressure impulses around the columns of the platform are estimated. When a wave hits the deck, the structure experiences a positive slamming dominated lifting force during the initial water entry phase, followed by a negative force during the water exit phase. The force in the latter phase is dominated by a negative added mass force due to negative fluid particle accelerations and its magnitude may be larger than the positive force peak. The water exit phase is important for global structural effects, while the initial impact yields the highest pressures and is critical for local structural responses. The force magnitude is highly dependent on wave amplitude and wave period. Simulations are performed in ANSYS Fluent and input parameters, modelling approach and assumptions are thoroughly described in the report. Ultimately, the results from the CFD simulations agree well with the empirical model tests and ANSYS Fluent is proved to be a powerful tool predicting wave-in-deck loads. It yields very satisfactory results for water entry, but slightly less for water exit. Conclusions drawn from the study are that quality of the mesh and time step size clearly influence the results and it can be difficult to model turbulence correctly, due to numerical diffusion of the waves.
Keywords: Transportteknik och logistik; Transport Systems and Logistics